2017
DOI: 10.1097/md.0000000000005626
|View full text |Cite
|
Sign up to set email alerts
|

Validations and psychological properties of a simplified Chinese version of pain anxiety symptoms scale (SC-PASS)

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Consistent with previous studies, patients with the comorbidity of MDD and CP had more pain-related anxiety symptoms than patients in the depression and control groups ( 6 , 30 ). Although previous studies on depression showed that pain-related anxiety can induce pain experience, they did not investigate its accuracy ( 31 ).…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies, patients with the comorbidity of MDD and CP had more pain-related anxiety symptoms than patients in the depression and control groups ( 6 , 30 ). Although previous studies on depression showed that pain-related anxiety can induce pain experience, they did not investigate its accuracy ( 31 ).…”
Section: Discussionsupporting
confidence: 90%
“…However, one shortcoming of conducting pain research in China is the lack of validated questionnaires. To our knowledge, eight pain-related questionnaires have been translated from English into SC which includes, Beck Depression Inventory (BDI), 26,27 Chronic Pain Acceptance Questionnaire, 28,29 the Leeds Assessment of Neuropathic Symptoms and Signs, 30,31 McGill Quality-of-Life Questionnaire (McGill), 32,33 the Oswestry Disability Index (ODI), 34,35 the Pain Anxiety Symptoms Scale (PASS), 36,37 the Pain Sensitivity Questionnaire (PSQ), 38 and the Positive and Negative Affect Schedule (PANAS). 39 Although a Traditional Chinese version of PCS 20 was created in Hong Kong, it was not adopted in Mainland China due to cross-cultural differences between Mandarin and Cantonese.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that chronic low back pain may seriously affect the sleep quality of patients who have been experiencing pain for a long time and may lead to adverse psychological reactions, such as fear avoidance belief, we included the 36-item Short-form Health Survey, 34 Self-rating Anxiety Scale, 35 Zung Self-Rating Depression Scale, 36 Pittsburgh Sleep Quality Index, 37 Pain Anxiety Symptoms Scale, 38 Tampa Scale for Kinesiophobia, 39 , 40 Fear Avoidance Beliefs Questionnaire, 41 minimal clinically important difference in pain and function, 42 , 43 global perceived effect, 44 , 45 adverse events, and participants’ recommendation levels on the intervention that they received as the secondary outcomes. Details on the outcome measures are presented in Supplement 1 .…”
Section: Methodsmentioning
confidence: 99%